Mapping the Research Landscape of Overseas Chinese Literature: Trends and Hotspot from 2006 to 2025 (KEMANUSIAAN The Asian Journal of Humanities, 2026)
Overseas Chinese literature embodies the historical memory, identity negotiation and cultural expression of diasporic Chinese communities within transnational and cross-cultural contexts, making it an essential component of globalisation and diaspora studies. However, its overall research framework has not yet been systematically reviewed. Existing studies in this field remain thematically fragmented and methodologically limited, highlighting the urgent need for bibliometric and visualised analyses to reveal its research hotspots and evolutionary trends. This study analyses 397 publications retrieved from the Web of Science Core Collection (2006–2025) using CiteSpace software and integrates keyword co-occurrence, clustering and timeline mapping techniques within the theoretical framework of globalisation and diaspora studies. The findings indicate a clear evolution from early focuses on immigrant identity and ethnic characteristics to more diversified themes such as gender politics, cultural hybridity and transnational writing, with transnationalism emerging after 2019 as the dominant analytical paradigm in the field. These results not only map the knowledge structure and evolutionary trends of overseas Chinese literature but also demonstrate how integrating globalisation and diaspora theories with bibliometric methods can provide a systematic foundation and analytical framework for future cross-cultural and interdisciplinary research.